Toward a wild pollinator strategy for Canada: expert-recommended solutions and policy levers - Rachel Nalepa; Sheila R. Colla (Canadian Science Publishing, 2023)
Invertebrate pollinators are in trouble: particularly documented are declines among bees and butterflies. Interacting stressors include pesticides, pathogens, habitat loss, nonnative species, and climate change. Many governments have strategies to reduce negative pressures on pollinators, but Canada does not despite widespread public interest in pollinator health. This study serves as a needs assessment for science-based policy solutions for wild pollinator conservation in Canada. We designed a Policy Delphi survey technique to identify solutions that experts deem both desirable and feasible. Our secondary aim was to identify research priorities that would inform the implementation of these solutions. Sixty % of the 83 unique solutions were supported and feasible at a high consensus level (10% were "strongly" supported and "definitely" feasible). General themes included improving the Canadian government's approach in assessing pesticide risk to pollinators, curbing pathogen spillover/spillback between managed and wild pollinators, and reducing the reliance of Canadian agricultural systems on pesticides, among others. We discuss solutions in reference to pollinator conservation policies recommended by the broader scientific community and identify policy levers within the context of Canada's highly decentralized approach to biodiversity conservation/management and a political economy that uses high numbers of managed, mostly nonnative bees for pollination services.